INTRODUCTION OF THE STANDARD GOST 8.586 (1–5)-2005 FOR MEASURING OF CONSUMPTION AND QUANTITY OF LIQUIDS AND GASES WITH THE HELP OF STANDARD RESTRICTIONS - T. V. Ivanets; E. V. Borisenko (Литьë и металлургия)
It is shown that putting into operation of complex of intergovernmental standards GOST 8.586(1-5)-2005 regulating application of measuring complexes on the basis of restriction, enables to improve precision of measurements of consumption and quantities of liquids and gases.